Physic properties test for variations in the addition of kelor rods (moringa oleivera) on the lis of gypsum profile - Ety Jumiati; Abdul Halim Daulay; Tri Ninda Malika (Universitas Islam Negeri Sumatera Utara Medan, 2021)
Research on composite materials has been carried out with variations in the addition of Moringa stems to the gypsum profile trim. And tested for variations in the composition of the mixture of Moringa stem fiber and gypsum flour, including: sample A (0% : 100%), sample B (2% : 98%), sample C (4% : 96%), sample D (6% : 94%), sample E (8% : 92%), sample F (10% : 90%) with FAS 0,5. The results of the characterization of the gypsum profiles produced on the physical properties test: density of 1.00-1.24 g/cm3. The value of water absorption is 24-45%. And the thickness development value is 2.27-4.82%, which meets the value of SNI 01-4449-2006. From the research data, the best sample is sample B with a density value of 1.14 g/cm3, the water absorption value is 27%, the thickness expansion value is 3.45%.Keywords :gypsum flour, list profil gypsum, moringa fiberThere has been a study of composite materials with variations of additionsKelor bars on the gypsum profile. And testing compound variationsKelor stem fibers and gypsum flour, among others: sampela (0%: 100%),Sample b (2% 98%), sample c (4% : 966), samel d (6%: 94%), sample e (8%92%), sample f (10% 90%) with fas 0.5. The fine print is the gypsum profileProduced on the test of frisis nature: a density of 1.00-1.24 g/cm3. Power valueAbsorption of 2445% water. And 2.27-4.82% thick development value, whichEnacting value o1-4449-2006. From the research data generated that sampleBest is on sample b with a density value of 1.14 g/cm, the value of permeable water279%, thick development value 3.45%.